Social transformation in the cruise industry during the COVID-19 pandemic - Yip, Tsz Leung; Lau, Yui-yip; Kanrak, Maneerat (Frontiers in Marine Science, 2023)
Social transformation is an emerging trend and a new phenomenon in the cruise industry in the 21st century. Cruise lines encounter stiff competition with many competitors and face sophisticated and unpredictable challenges from the wave of social transformation. Furthermore, the outbreak of the COVID-19 pandemic has accelerated the social transformation phenomena in the industry. This study investigates how social transformation reshapes the cruise industry to discuss the remarkable social and economic changes in the industry. The study builds upon the 4C descriptive framework to suggest how cruise lines take measures to create resilience against the influence affected by social transformation. The study is conducted through 18 semi-structured and in-depth interviews with cruise terminals, travel agencies, logistics, and tourism associations, researchers, cruise lines and passengers, and airlines. The cruise shipping industry structure has fundamentally shifted from supply-driven to demand-driven. The concept of social transformation becomes vital and is a driving force that is more society specific. Findings are drawn as valuable guidelines for cruise lines to scale up in operations and strategies that create social transformation. Cruise lines can also maintain sustainable development and resilient recovery post-COVID-19